MORAL AND SPIRITUAL GUIDANCE ON PRISONERS (CASE STUDY AT CORRECTIONAL INSTITUTION CLASS IIA PEKANBARU) - Try Wiganda Irfan; Hasrul Hasrul; Isnarmi Isnarmi (Jurnal Ilmiah Al-Syir'ah, 2019)
This study discusses the process of moral and spiritual coaching in correctional institution class IIA Pekanbaru. The purpose of the research is to know and analyze the form of implementation of moral and spiritual coaching in Correctional Institution class IIA Pekanbaru. This research has a descriptive method with a qualitative approach. Data collection techniques are through interviews, documentation, and observation of officials, prison officers, Dai, and priests and convicts. The results showed that the form of moral and spiritual coaching in inmates in the prison class IIA Pekanbaru is preaching (da’wah). Da’wah and imprisonment have the same role as the moral and spiritual coaching in order to form the whole person and restore human rights to socialize with the community.